growth pattern and the industrial development of the lagos region, nigeria - Dickson Dare Ajayi (Indonesian Journal of Geography, 2004)
This paper examines the nature, growth and spatial pattern of industries within the Lagos Region. Industrial activities in this region grew progressively over the year from mere brickwork, palm oil mills, printing press, soap factory, and metal container factory to capital intensive manufacturing. Indeed, the number of industrial establishments increased from 122 in 1962 to 637 in 1993. Lagos developed into Nigeria's leading industrial center; especially following the expansion in its service and administrative sectors. Whereas, chemicals and pharmaceutical; and basic metal, iron and steel and fabricated metal products industry groups dominate in industrial scene, wood and wood products (including furniture); and non-metallic mineral products are rare. The spatial pattern shows that industrial establishments vary amongst the industrial estates/areas, and also among the industry groups. Ikeja/Ogballsheri industrial estate/area dominates the industrial scene.